A political economy for the "true republic". The Revista de Economia Argentina in the 1920s - Bacolla, Natacha Cecilia (Universidad Nacional del Litoral, 2020)
Within the active publishing world of the early 20th century, the Revista de Economía Argentina was a long-lasting project with a multiple intervention aimson the public space that would extend from 1918 to 1952. This article focuses on the review first decade, a moment that coincided with the global scenario of changes unleashed by the first post-war period and at the national level with the experience of radical governments made possible by the electoral reform. Firstly, the text analyses the actors, networks and legitimating mechanisms that had sustained the beginnings of the review. Secondly, it examines the conceptual constructions it had spread in these early years. It argues that in the field of social knowledge and its translation into policy tools, rather than identifying with a «Copernican revolution» in terms of notions regarding State interventionism, economic nationalism, monetary and sectoral policies, it was part of a more complex process of conceptual and practical changes, still in the frameworks of liberal political economy.